Graded response of the pulmonary circulation to progressive pulmonary embolism in sheep: From compensation to lethal right heart failure - Cheng Zhou, MD; Yuman Li, MD; Kyle Polley; Cherry Ballard-Croft, PhD; Masashi Kawabori, MD; Keshava Rajagopal, MD, PhD; Joseph B. Zwischenberger, MD; Dongfang Wang, MD, PhD (JHLT Open)
Background: Severe pulmonary embolism (PE) with right heart failure (RHF) has high mortality. To more fully understand PE progression, we evaluated the right ventricle (RV) and pulmonary circulation response to graded PE in an acute PE sheep model. Methods: Polydextran beads were intravenously administered every 15 minutes in 250 mg doses to adult female sheep (n = 8) until death. Concurrent pulmonary artery (PA) blood flow/pressure was measured. RV pressure-volume (P-V) loops were generated with a conductance catheter. Pulmonary vascular resistance was used to stage PE severity into mild, moderate, and severe groups. Results: All sheep developed graded RHF. For mild, moderate, and severe PE, 3, 6, and 9 doses were needed, respectively. Only 1 additional dose triggered death. In severe PE, mean PA pressure reached 42 ± 6 mm Hg with significantly decreased cardiac output (CO). Pulmonary impedance spectra showed significantly increased Z0 (RV static load) and Z1 (RV pulsatile load). PE shifted the RV P-V loop from lower left triangular to upper right rectangular shape. PA elastance (Ea, RV afterload) and end-systolic elastance (Ees, RV contractility) progressively increased. Ees/Ea (RV-PA coupling) was initially maintained but became uncoupled in severe PE, causing RHF. Conclusions: Compensatory increases in RV contractility initially maintain CO in PE despite RV afterload elevation. Increased RV contractility eventually fails to compensate for elevated RV afterload, causing RV-PA uncoupling in severe PE with RHF. Severe PE rapidly progresses to lethal RHF and will likely require immediate intervention to prevent death.